(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Hyperuricemia is associated with higher mortality in patients suffering from hypertension, coronary heart disease, cerebrovascular events, metabolic syndrome, insulin resistance, gout and renal stone formation and it is more in individuals with diabetes. The prevalence of hyperuricemia is high in T2DM. The aim of the present study was to assess the relationship between hyperuricemia and blood pressure in T2DM subjects and thus to help the clinician for early diagnosis, treatment and to prevent further complications. Total 350 study subjects were enrolled for this study; among them 203 were T2DM with normal level of serum uric acid level and 147 were T2DM with high serum uric acid level. It was observed that systolic blood pressure was significantly higher (134.5±9.6 mm of Hg) in T2DM with hyperuricemia (p<0.001) than T2DM with normal serum uric acid level (123.3±10.9 mm of Hg). On the other hand diastolic blood pressure was significantly higher (87.1±5.9 mm of Hg) in T2DM with hyperuricemia (p<0.001) than T2DM with normal serum uric acid level (79.6±8.3 mm of Hg). Age (years) showed no significant difference between T2DM with serum uric acid<7 mg/dl and T2DM with serum uric acid>7 mg/dl (p<0.05). In our study it was revealed that males were in greater risk of developing hyperuricemia. BMI was significantly (p<0.001) greater in T2DM subjects who had normal serum uric acid level (27.9±3.8) than with those who had serum uric acid>7 mg/dl (24.4±3.83). No significant differences were found in FBS, blood sugar 2 hours after breakfast, HbA1C, serum creatinine and blood urea between groups. Bangladesh J Med Biochem 2016; 9(2): 49-53